Early treatment of symphysis mandibular fracture in 12 years old children using erich arch bar: a case report - Syahril Samad; Winarno Priyanto (DiscoverSys Inc., 2017)
Objective: To explain the management of symphysis mandibular fracture in pediatric using erich arch bar.Methods: A 12 years old boy has fracture in mandible due to the accident occurred when his chin hit the touching motorcycle tank. Clinically a deformity at the anterior of mandible and malocclusion has occurred. Patient also complained a pain with swelling and bleeding at the region of fracture and lip. Suturing had been done in wound area for both intra and extra oral area followed by the application of arch bar in maxilla and mandible. Doing evaluation at the third day, a vague fracture line was found in panoramic radiograph.Results: The following treatment done was the application of erich arch bar for mobility reducing the fracture of mandibular symphysis. A good healing act management to symphysis mandibular fracture of 12 years old children with full eruption of teeth has been given to the teeth to develop retention and to stabilize the erich arch bar.Conclusion: Management of pediatric symphysis mandibular fracture for 12 years old children with full eruption of teeth using erich bar revealed a healed fracture.Â